1977
DOI: 10.2172/5247196
|View full text |Cite
|
Sign up to set email alerts
|

Radiation cytogentics of the yellow-fever mosquito Aedes aegypti and the plant genus Collinsia. Final report, April 1967--September 1977

Abstract: Final report on ERDA Supported Research Project on "Radiation Cytogentics of the yellow-fever mosquito Aedes degypti and the plant genus Collinsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several problems have been already suggested as causal of the low quality of polytene chromosomes preparations which could be suitable for analysis in Aedes and Culex: (1) Sutton (1942) suggested the presence of weak points, which can be assumed now as being heterochromatic areas where the chromosomes break easily (Semeshin et al 2001); (2) the great length of chromosome arms (Kitzmiller 1963) should influence chromatic interactions; (3) the inter-and intra-chromosomal connections, or ectopic pairing (French et al 1962, Verma et al 1987 resulting from regions of highly repetitive DNA (Rai & Black IV 1999); (4) surface adhesions (Rai 1967apud Sharma et al 1978) that have been observed in Anopheles funestus and is dependent on β-heterochromatin (Sharakhov et al 2001) and (5) asynapsis observed in the polytene complement (Zambetaki et al 1998). …”
mentioning
confidence: 99%
“…Several problems have been already suggested as causal of the low quality of polytene chromosomes preparations which could be suitable for analysis in Aedes and Culex: (1) Sutton (1942) suggested the presence of weak points, which can be assumed now as being heterochromatic areas where the chromosomes break easily (Semeshin et al 2001); (2) the great length of chromosome arms (Kitzmiller 1963) should influence chromatic interactions; (3) the inter-and intra-chromosomal connections, or ectopic pairing (French et al 1962, Verma et al 1987 resulting from regions of highly repetitive DNA (Rai & Black IV 1999); (4) surface adhesions (Rai 1967apud Sharma et al 1978) that have been observed in Anopheles funestus and is dependent on β-heterochromatin (Sharakhov et al 2001) and (5) asynapsis observed in the polytene complement (Zambetaki et al 1998). …”
mentioning
confidence: 99%